Effects of farmyard manure (FYM) and blended NPSB fertilizer rate on growth and yield of potato (Solanum tuberosum L.) in Gewata, Kaffa, southwest Ethiopia - Mengesha, A.; Negash, T.; Abebe , J. K. (International Journal of Horticultural Science, 2024)
Potato (Solanum tuberosum L.) is an essential crop for nutrition and food security and generating income to small-holder farmers in Ethiopia. Productivity of the crop is, however, limited by poor nutrient management practices and low soil fertility. In most parts of potato growing areas of Ethiopia, soil are deficient in macro (nitrogen, phosphorus and sulfur) and micro nutrients (boron) which are known to affect production and productivity of potato. A field trail was accompanied to determine the growing response of potatoes ’Belete varieties’ to combine the treatment of farmyard manure and blended NPSB (nitrogen, phosphorous, sulfur and boron) fertilizer at Gewata, southwest Ethiopia during 2019/2020 main cropping season. The variables are laid out four level of farmyard manure (0, 5, 10 and 15 t/ha) and four level of blended NPSB fertilizer (0, 50, 100, and 150 kg/ha). The treatments were organized in a completely randomized block design with three replications using a 4x4 factorial layout. SAS (version 9.4) was used for data were analyzed. The finding indicate that, combined application of FYM (farmyard manure) with NPSB significantly (p